(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research is considered a completion to many studies which dealt with nunnation as a tool of namelessness as Arabic scientists were clearly interested in nunnation in their artistic texts and books to control its origins and feel its effect in the lingual context. Research about nunnation origins has stopped in the semetic languages, generally speaking, and in Arabic in particular. After that its linguistic and conventional meaning was known by grammarians, linguals and eloquent people. It also spotlighted all its kinds, the linguists disagreement about its number and indication of each kind of it projecting its significance efficacy in reference to namelessness as a tool that is opposite to the definite article ( alef and lam ) . In addition to show the obstacles that faced grammarians as proper names nunnation which is considered as a part of identifiers to know its omission places which were identified by grammarians .